Penerapan Metode Mubasyarah dalam Meningkatkan Maharah Istima’ dan Maharah Kalam pada Pembelajaran Bahasa Arab Bagi Santri PDF Ulya’ DDI Mangkoso - Ilham; Haniah; Chalik, Sitti Aisyah (Journal of Arabic Education and Linguistic, 2025)
This study uses a quantitative approach with the Pre-Experimental method, involving all 32 students of Class XI in 2024 as the research population. Data collection was carried out through tests and documentation, while data analysis used descriptive and inferential methods. The results of the Independent Samples Test statistical test showed that the Mubasyarah method was significantly more effective than conventional learning methods. Students who studied with the Mubasyarah method obtained higher average scores in the skills of maharah kalam (speaking) and maharah istima' (listening), with smaller variations in values, indicating better consistency in learning outcomes. Overall, this study proves that the Mubasyarah method is able to improve students' understanding of the material and learning outcomes in Arabic language skills more optimally than conventional methods. The implications of this study open up opportunities for further research to explore the effectiveness of the Mubasyarah method in developing other Arabic language skills, such as maharah qira'ah (reading) and maharah kitabah (writing), in order to gain a more comprehensive understanding of the impact of this method on Arabic language learning as a whole.